2010
DOI: 10.1002/pola.23991
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of nitroxide radical coupling reactions mediated by CuBr

Abstract: In a previous paper, we described the room temperature rapid, selective, reversible, and near quantitative Cu‐activated nitroxide radical coupling (NRC) technique to prepare 3‐arm polystyrene stars. In this work, we evaluated the Cu‐activation mechanism, either conventional atom transfer or single electron transfer (SET), through kinetic simulations. Simulation data showed that one can describe the system by either activation mechanism. We also found through simulations that bimolecular radical termination, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…The peak at M p3 (9490) did not change with time and was most likely attributable to a cyclic structure consisting of two PSTY chains coupled together by two dinitroxide linkers. It was very unlikely that the cyclic structures formed by the bimolecular termination of two chain end radicals [5] because of the very low probability of the simultaneous activation of both ends of a PSTY chain to radicals. The decoupling experiments described below support this assertion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The peak at M p3 (9490) did not change with time and was most likely attributable to a cyclic structure consisting of two PSTY chains coupled together by two dinitroxide linkers. It was very unlikely that the cyclic structures formed by the bimolecular termination of two chain end radicals [5] because of the very low probability of the simultaneous activation of both ends of a PSTY chain to radicals. The decoupling experiments described below support this assertion.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic simulations showed that the concentration of Cu II Br 2 from this type of reaction increased linearly with conversion. [5] In a feed process, Cu I Br has time to disproportionate, allowing the copper species to reach their equilibrium concentrations. This resulted in a high Cu II Br 2 concentration at the initial stage of the reaction, in which deactivation of the chain-end radicals by Cu II Br 2 now successfully competed with nitroxide trapping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, milder conditions were investigated and good results were achieved after the discovery of single electron transfer living radical polymerization . Accordingly, SETNRC, which relies on the formation of carbon‐centered radicals by single electron transfer reaction and successive trapping by nitroxide radicals, emerged as a new and efficient strategy for polymer coupling . In SETNRC, Cu(0)/PMDETA is generally used as a catalyst system to generate macroradicals at ambient temperature.…”
Section: Development Of Novel Macromolecular Architectures By Nrc Reamentioning
confidence: 99%